Features of the Formation of the Epidermal Barrier and the Use of Emollients in Premature and Young Children - Nikolay N. Murashkin; Roman A. Ivanov; A. A. Savelova; D. V. Fedorov; Leonid A. Opryatin; W. Ahmad (Union of pediatricians of Russia, 2019)
The article presents modern data on the features of the structure of the skin and the formation of the epidermal barrier in premature and young children. Information is given regarding changes in the properties of the skin: microrelief, hydration, transepidermal water loss, acidity, content of the natural moisturizing factor, and sebum secretion. Attention is also paid to the role of vernix caseosa in the formation of a mature epidermal barrier and data on the use of emollients are provided.